The Influence of Embodiment as a Cartoon Character on Public Speaking Anxiety - Bellido Rivas, Anna I.; Navarro, Xavi; Banakou, Domna; Oliva, Ramon; Orvalho, Veronica; Slater, Mel (Frontiers in Virtual Reality, 2021)
Virtual Reality can be used to embody people in different types of body – so that when they look towards themselves or in a mirror they will see a life-sized virtual body instead of their own, and that moves with their own movements. This will typically give rise to the illusion of body ownership over the virtual body. Previous research has focussed on embodiment in humanoid bodies, albeit with various distortions such as an extra limb or asymmetry, or body of a different race or gender. Here we show that body ownership also occurs over a virtual body that looks like a cartoon rabbit at the same level as embodiment as a human. Furthermore we explore the impact of embodiment on performance as a public speaker in front of a small audience. Forty five participants were recruited who had public speaking anxiety. They were randomly partitioned into three groups of 15, embodied as a Human, as the Cartoon rabbit, or from third person perspective (3PP) with respect to the rabbit. In each condition they gave two talks to a small audience of the same type as their virtual body Several days later, as a test condition, they returned to give a talk to an audience of human characters embodied as a human. Overall, anxiety reduced the most in the Human condition, the least in the Cartoon condition, and there was no change in the 3PP condition, taking into account existing levels of trait anxiety. We show that embodiment in a cartoon character leads to high levels of body ownership from the first person perspective and synchronous real and virtual body movements. We also show that the embodiment influences outcomes on a public speaking task.